High Social Piety and Tolerance Indices Among a Multireligious Society: Evidence from Sumenep, Indonesia - Sri Rizqi Wahyuningrum; Mohammad Ali Al Humaidy; Reza Mubarak; Siti Mariyam; Mohammad Zaini Bin Yahya (Jurnal Dialog, 2026)
Social piety in religious traditions is considered a moral obligation that must be carried out by every individual. Social piety is part of a process of defining Islamic worship in a contemporary context. As is the case in Sumenep Regency, this practice is well-maintained, but challenges in maintaining social and moral values ​​remain. News about immoral acts, such as murder, rape, and corruption, often appears in the media and indicates a humanitarian crisis that requires attention. Therefore, it is necessary to measure and evaluate through the Social Piety Index and the Tolerance Index of Sumenep Regency. This study uses a mix-methods approach. The respondents were residents of Sumenep Regency, using multistage random sampling (400 respondents). Data analysis was conducted using descriptive statistics and index analysis. The results showed that the Social Piety Index of the Sumenep Regency Community reached a score of 85,91. This figure represents the condition of the community successfully creating a harmonious, caring, and mutually supportive social atmosphere. Second, the tolerance index with a score of 87,95, the community feels harmonious social relations and mutual respect for differences. This achievement illustrates a strong foundation for realizing social harmony as a main pillar in the development vision of Sumenep Regency.